2021
DOI: 10.3390/e23111531
|View full text |Cite
|
Sign up to set email alerts
|

Katz Fractal Dimension of Geoelectric Field during Severe Geomagnetic Storms

Abstract: We are concerned with the time series resulting from the computed local horizontal geoelectric field, obtained with the aid of a 1-D layered Earth model based on local geomagnetic field measurements, for the full solar magnetic cycle of 1996–2019, covering the two consecutive solar activity cycles 23 and 24. To our best knowledge, for the first time, the roughness of severe geomagnetic storms is considered by using a monofractal time series analysis of the Earth electric field. We show that during severe geoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…In this work, basing on the review of literature and continuing our previous studies [32,45], we initially compared a few methods: the Katz algorithm [11], which revealed discriminating power [32,38], its modifications [46,47], Higuchi method [12], Structure Function scaling [18,[48][49][50], and Detrended Fluctuation Analysis [15,51].…”
Section: Fractal Methods Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, basing on the review of literature and continuing our previous studies [32,45], we initially compared a few methods: the Katz algorithm [11], which revealed discriminating power [32,38], its modifications [46,47], Higuchi method [12], Structure Function scaling [18,[48][49][50], and Detrended Fluctuation Analysis [15,51].…”
Section: Fractal Methods Selectionmentioning
confidence: 99%
“…Gil et al [32] considered geomagnetic field components and modelled geoelectric field for the Belsk mid-latitude station during the full solar magnetic cycle of 1996-2019. Katz fractal dimension technique was applied in moving windows of 60 min and a significant increase in roughness (Katz dimension) of the analysed characteristics during severe geomagnetic storms was revealed.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, and its easy implementation [ 38 ], the use of the Katz fractal dimension is proposed in this work. This index has been used in different applications, such as the detection of faults on induction motors [ 38 ], the study of the geoelectric field of the earth during severe geomagnetic storms [ 39 ], and speech emotion classification [ 40 ].…”
Section: Materials and Methodsmentioning
confidence: 99%
“…However, this method cannot catch the sudden changes happen in the irregular time-series datasets [71]. To explore the complexity of scale-free time-series data, a variety of different nonlinear techniques such as Higuchi algorithm, power spectrum analysis, and Katz algorithm have been highlighted in different areas [72][73][74][75][76][77]. To approximate the complexity index of Drought Monitor Categories database, we utilize the Higuchi Algorithm [72].…”
Section: Higuchi Fractal Dimension Algorithmmentioning
confidence: 99%